Modinomics : inclusive economics, inclusive governance - Kochhar, Sameer (Haryana, India : Skoch Media, 2014)
"This book presents the vision behind Modi's thought process, and the action on the ground in terms of actual field reports and case studies. The book seeks to highlight the economic and development strategies adopted by Modi. The learnings from these would stand other states in good stead. Under Modi, Gujarat stands out for its long-term vision and impeccable execution. Governance is clearly not just about lofty speeches and promises but actual delivery; as is economics. One of the key ideas that the book brings out is that Modi is a proponent of both Inclusive Economics as well as Inclusive Governance. This in a sense is the essence of ModiNomics, a new phenomenon, which is discussed in the book."--Back cover.
Introduction: understanding Narendra Modi -- The essence of modinomics -- Galvanising growth -- Building infrastructure -- Agricultural revival -- Developing human capital -- Growth at the grassroots --Sustainable development -- Conclusion.
Includes bibliographical references and index.
Keywords: Modi, Narendra, -- 1950-; Economic development -- India -- Gujarat; Gujarat (India) -- Economic conditions -- 21st century; Gujarat (India) -- Economic policy -- 21st century; Gujarat (India) -- Politics and government -- 21st century